The quality of daylight in various types of residential buildings (2019)
The residential building design must place an emphasis on daylight in interiors, in terms of quality as well as quantity. The legislative requirements are more or less unified across the spectrum of residential building types. The article compares the daylighting conditions in three different types of residential development in Prague: a tenement house from the 19th century, a neighbourhood of precast panel buildings from the second half of the 20th century and a contemporary housing complex. The urban situation, such as distances between the buildings and street profiles, majorly influences the daylight and insolation in the apartments. The apartment layout, the proportions of the room and the size and proportion of the windows are also important factors affecting the distribution of daylight in the rooms. The case study is a part of a larger research project, which aims to create a supplementary teaching material for architecture students, who are learning to design the suitable interiors.